French thought and the critical work of Jorge Aguilar Mora (Revista de Crítica Literaria Latinoamericana, 2013)
This article focuses on the importance of 1960s and 70s French thought, particularly that of Roland Barthes and Gilles Deleuze, in the work of Jorge Aguilar Mora: his reading of Octavio Paz's essayistic work and his reevaluation of the Mexican Revolution as a rebellious event. An analysis of La divina pareja. Historia y mito en Octavio Paz (1978) and of Una muerte sencilla, justa eterna. Cultura y guerra durante la Revolución Mexicana (1990) sheds light on Aguilar Mora's theoretical concerns, particularly the need to overcome analogical reasoning with respect to the question of Identity, and the need to reevaluate the revolutionary experience beyond the modes of representation framed by historicism.
Keywords: Jorge Aguilar Mora; Friedrich Nietzsche; Octavio Paz; Mexican Revolution; nationalism; Roland Barthes; Gilles Deleuze